Efficacy of DHA and EPA on Serum Triglyceride Levels of Healthy Participants: Systematic Review - Kawasaki Yohei; Iwahori Yoshihiro; Chiba Yosuke; Mitsumoto Hiroyuki; Kawasaki Tomoe; Fujita Sumiko; Takahashi Yoshinori (International Journal of Nutrition, 2019)
Background Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are categorized as omega-3 poly unsaturated fatty acids (PUFAs) that are present in fish oil, etc. DHA and EPA omega-3 PUFAs have a well-established fasting serum triglycerides (TG) lowering effect that may result in normal lipidemia in hyperlipidemic patients. In general, omega-3 PUFAs, such as DHA and EPA, can be ingested easily, and because they are highly safe, they are assumed to be suitable for controlling fasting serum TG in the serum of those who do not require drug treatment. To the best of our knowledge, however, almost all systematic reviews on the effects of omega-3 PUFAs on lowering fasting serum TG are directed at patients fulfilling the diagnostic criteria of dyslipidemia. Objectives To review and confirm the preventive effect of omega-3 PUFAs against hypertriglyceridemia or the effect on nondrug treatment in patients with a mild disease, a systematic review was conducted to determine whether there was a fasting serum TG-lowering effect in subjects without disease and those with a slightly higher triglyceride level who consumed DHA and/or EPA orally compared to those with placebo or no intake of DHA and/or EPA. Search Methods We evaluated articles from searches of PubMed (1946-February 2016), Ichushi-Web (1977-February 2016), and J Dream III (JST Plus, 1981-February 2016; JMED Plus, 1981-February 2016). The keywords were set as follows: “DHA” or “docosahexaenoic acid” or “EPA” or “eicosapentaenoic acid” and “TG” or “triglyceride” or “triglycerol” or “triacylglycerol” or “neutral lipid.”. In addition to the literature group obtained by the database search, we included participants not suffering from any disease (i.e., excluding mild hypertriglyceridemia). Eligibility Criteria Before the test selection process, the following inclusion criteria were defined. Participants were healthy men and women including those with mild hypertriglyceridemia (fasting serum TG level, 150-199 mg/dL [1.69-2.25 mmol/L)). Intervention was defined as orally ingested DHA and/or EPA. Comparison was made to placebo intake or no intake of DHA and/or EPA. Results were measured for the fasting serum TG level. The test design was RCT, and quasi-RCT. Data Abstraction Various characteristics were extracted from original reports using a standardized data extraction form, including the author of the study, research year, research design, subject characteristics (sex, age, sample size), period, dose of DHA and/or EPA (mg/day), and comparison group. Main Results We identified 37 documents for review. Among the 37 reports used to integrate literature results, 25 revealed a decrease in fasting serum TG level ​​due to the oral ingestion of DHA and/or EPA. Sixteen studies on subjects without disease and 21 on subjects with slightly higher fasting serum TG levels were separated and stratified analysis was conducted. Ten of the 16 (normal TG participant) and 15 of the 21 studies (slightly higher TG participant) respectively, indicated that at least 133 mg/day of DHA and/or EPA intervention provided a statistically significant decrease in the fasting serum TG level between an intervention group versus a placebo group.
Keywords: docosahexaenoic acid